Polarity and peacekeeping: The effect of the international structure on United Nations peacekeeping missions - Appleton, Abigail (AUC Knowledge Fountain, 2015)
The end of the Cold War produced a significant shift in the structure of the international system. It also witnessed an increased use of peacekeeping as a mechanism to deal with conflicts. This increase is often attributed to a supposed “changing nature of conflict,” where intra-state war has become more common than the classic inter-state war and conflict has become more violent, brutal, and complicated. However, these descriptions leave important aspects of peacekeeping operations unexplained. A better explanation is needed for the international community’s increased intervention in conflicts. This thesis argues that the bipolar international structure of the Cold War placed restrictions on the way United Nations peacekeeping was created and performed. The end of the Cold War and the consequent changes in the international structure explain the shift in peacekeeping that occurred in the 1990s. As the structure of the international system has continued to evolve in the 21st Century, peacekeeping has also shifted. The institution of peacekeeping, itself a response to conflict by the international system, has become what it is because of the changes in the structure of the international system. Any future shift to a bipolar or multipolar structure will again affect the way peacekeeping functions.